(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The per capita energy consumption in any country is an index of the living standard of the people of that country. Electric energy is an essential ingredient for the industrial and all-round development of any country. The increasing use of electrical energy in different fields of daily life has been primarily due to the availability of a vast variety of electrical machinery for the purpose of generation and utilization. It is a coveted form of energy, because it can be generated centrally in bulk and transmitted over long distances without much difficulty. This energy is obtained by conversion from fossil fuels (coal, oil, natural gas), the nuclear and hydro sources. Heat energy dissipated from the burning of fuels or nuclear fission is first converted to mechanical energy and then this mechanical energy is converted into electrical energy via generators. In power plants, these generators may be a hydro generator or a turbo generator, depending on the plant requirements.